2013
DOI: 10.1063/1.4789391
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared photodetection of β-FeSi2/Si heterojunction photodiodes at low temperatures

Abstract: n-type β-FeSi2/p-type Si heterojunction photodiodes were fabricated by facing-targets direct-current sputtering, and their near-infrared photodetection properties were studied in the temperature range of 50–300 K. At 300 K, devices biased at −5 V exhibited a current responsivity of 16.6 mA/W. The measured specific detectivity was remarkably improved from 3.5 × 109 to 1.4 × 1011 cmHz1/2/W as the devices were cooled from 300 K down to 50 K. This improvement is mainly attributable to distinguished suppression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
6
43
1
Order By: Relevance
“…The leakage current was reduced dramatically with a decrease in temperature. This suppression should be attributed predominantly to the reduced carrier densityinβ-FeSi2 film sat low temperatures [2,4]. According to the significant difference in the carrier concentration between our β-FeSi2 films (1018 cm3) and Si substrates( 1015 cm3) [5], it can be assumed that the hetero junctions acted almost as a step junction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The leakage current was reduced dramatically with a decrease in temperature. This suppression should be attributed predominantly to the reduced carrier densityinβ-FeSi2 film sat low temperatures [2,4]. According to the significant difference in the carrier concentration between our β-FeSi2 films (1018 cm3) and Si substrates( 1015 cm3) [5], it can be assumed that the hetero junctions acted almost as a step junction.…”
Section: Resultsmentioning
confidence: 99%
“…n-Typeβ-FeSi2/p-type Si hetero junctions that showed good rectifying actions were employed as photodiodes [4].Then, it was confirmed that their photo detection performances were enhanced at low temperatures [5]. However, their carrier transport mechanism at low temperatures has never been studied.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The thin films of betaFeSi 2 created in this work presented n-type property as well as carrier density of approximately 5 × 10 17 cm -3 [9]. The produced hetero-structure between p-type Si wafers and n-type beta-FeSi 2 thin films can be utilized in photovoltaic and photodiode applications [10,11]. Despite the face beta-FeSi 2 possesses desirable properties for hydrophobic surface applications, there have been few studies or reports on the assessment of wettability properties of beta-FeSi 2 films produced via FTDCS for employment in such applications.…”
Section: Introductionmentioning
confidence: 99%
“…(11) Izumi et al (12) reported a near-infrared photodetection of β-FeSi 2 /Si heterojunction photodiodes with a responsivity of 16.6 mA/W. Therefore, in this study, the responsivity and quantum efficiency of p-Si/i-β-FeSi 2 /n-Si double-heterostructure photodiodes are investigated by self-developed analytical methods.…”
Section: Introductionmentioning
confidence: 99%